The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c8gc02811g
|View full text |Cite
|
Sign up to set email alerts
|

An innovative synthesis pathway to benzodioxanes: the peculiar reactivity of glycerol carbonate and catechol

Abstract: A peculiar reactivity of glycerol carbonate (GlyC) as an innovative and highly reactive alkylating agent for phenolic compounds is investigated in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…In literature, only a few studies focusing on the thermodynamic aspects of glycerol reforming [26] can be found. The overall process comprises several reactions with, according to recently published works, the primary reactions being [27] C3H8O3 → 4H2 + 3CO (∆H = 251 kJ/mol) glycerol decomposition (3) CO + H2O H2 + CO2 (∆H = −41 kJ/mol) water gas-shift reaction (4) The sum of Equations (3) and (4) corresponds to Equation (2). As previously described, glycerol reforming is an endothermic process (∆H = 128 kJ/mol) facilitated by high temperature, low pressure, and high water/glycerol ratio in the feed.…”
Section: C3h8o3 + 3h2o → 7h2 + 3co2mentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, only a few studies focusing on the thermodynamic aspects of glycerol reforming [26] can be found. The overall process comprises several reactions with, according to recently published works, the primary reactions being [27] C3H8O3 → 4H2 + 3CO (∆H = 251 kJ/mol) glycerol decomposition (3) CO + H2O H2 + CO2 (∆H = −41 kJ/mol) water gas-shift reaction (4) The sum of Equations (3) and (4) corresponds to Equation (2). As previously described, glycerol reforming is an endothermic process (∆H = 128 kJ/mol) facilitated by high temperature, low pressure, and high water/glycerol ratio in the feed.…”
Section: C3h8o3 + 3h2o → 7h2 + 3co2mentioning
confidence: 99%
“…Over the last decades, fossil fuels and their derivatives have remained the most widely exploited energy source for the world, with 97.6 million barrels/day in 2018 and an expected increase up to 112.2 million barrels/day by 2035 [1]. Environmental apprehension over global warming and the search for new sustainable alternatives to fossil energy have recently given rise to a sector of huge impact from the economic, scientific, and industrial standpoints, based on the use of biomass as feedstocks [2][3][4][5]. This sector, which bases itself on the 12 Principles of Green Chemistry [6], considers it imperative to develop eco-friendly and energy-efficient processes for the sustainable production of fuels and chemicals [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The instability of Cyrene in basic media, 34 and the use of PC as an alkylating agent for phenols have been reported. 35 Solvent recovery experiments were performed to study the feasibility of recycling of 1C after the reaction. Vacuum distillation proved to be a straightforward way to recover 1C with high purity (>99%) from the aqueous mother liquor (V water : V 1C = 10 : 3).…”
Section: Extending the Application Of Polarcleanmentioning
confidence: 99%
“…As a matter of fact, it is worth highlighting some recent research advances. The oxidation of chlorinated compounds by catalytic combustion on non-noble metals based oxides [4,5], NO x reduction to nitrogen or by selective catalytic reduction (SCR) with ammonia in the presence of heterogeneous catalysts [6]; biofuel production from vegetable oils [7]; the development of new active catalysts for Fenton and photo-Fenton processes [8]; the development of supported nanoparticle catalysts for the treatment of the emission of harmful substances from automobiles, and the use of waste as source of metals for catalysts preparation [9]; the design of new active catalytic systems for the preparation of olefins from polyols [10]; the catalytic hydrotreatment in the valorization of bio-oils obtained from lignocellulosic biomass pyrolysis [11]; and the design of active catalysts for the preparation of organic carbonates from CO 2 or bio-based compounds are some examples in this framework [12,13].…”
Section: Introductionmentioning
confidence: 99%